1997
DOI: 10.1046/j.1365-2036.1997.00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Four‐day quadruple therapy as a routine treatment for Helicobacter pylori infection

Abstract: Background: H. pylori eradication usually involves treatment with three or four drugs for at least 7 days. Possible advantages of short treatment regimens are better patient compliance and tolerability, and less adverse effects. Recently two reports have shown a cure rate of > 90% using a 4‐day quadruple therapy.Aim:To confirm these data and to evaluate the efficacy and tolerability of 4‐day quadruple therapy in a single centre.Methods:Thirty‐eight consecutive patients with non‐ulcer dyspepsia or peptic ulc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

1999
1999
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 4 publications
0
19
0
1
Order By: Relevance
“…Five studies to date have found a drop in efficacy in nitroimidazole‐resistant strains with these regimens; 33 –37 however, this was only significant in the largest published series by Van der Hulst et al 33 . All other studies, in which mostly only a few patients with nitroimidazole‐resistant strains were treated with quadruple therapy, have not found a drop in efficacy in case of nitroimidazole‐resistance 38 –47 . The reason for these discrepant results is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Five studies to date have found a drop in efficacy in nitroimidazole‐resistant strains with these regimens; 33 –37 however, this was only significant in the largest published series by Van der Hulst et al 33 . All other studies, in which mostly only a few patients with nitroimidazole‐resistant strains were treated with quadruple therapy, have not found a drop in efficacy in case of nitroimidazole‐resistance 38 –47 . The reason for these discrepant results is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, quadruple therapy is generally preceded by a 3‐day pre‐treatment with the proton pump inhibitor alone in order to allow this drug to reach a steady state concentration 10 , 11 and this was not done with ranitidine alone in our study. Considering the different pharmacokinetic properties of the two categories of antisecretory compounds, it is difficult to think that the lack of pre‐treatment with ranitidine could have determined the low success rate of the 4‐day RBC‐based triple therapy in our investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the treatment we investigated combines an antisecretory agent, such as ranitidine, with bismuth, clarithromycin and metronidazole, the eradication rate obtained is clearly lower than that observed with a proton pump inhibitor plus three antimicrobials given for the same very short period. 10,11 This difference is dif®cult to explain. It may be that the high prevalence of metronidazole and clarithromycin resistance in our geographical area 17 prevents the achievement of a high cure rate by a too short-lasting therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The eradication rate was similar if the same treatment was given for 4 days, but poor if the duration was further reduced to 2 days 14 , . 19 –23 We therefore designed a 3‐day quadruple therapy substituting tetracycline with clarithromycin, with no pre‐ or post‐treatment acid suppression. The short regimen was still able to achieve a high per protocol eradication rate of 94.3%.…”
Section: Discussionmentioning
confidence: 99%